Development of a fly ash-based geopolymeric concrete with construction and demolition wastes as aggregates in acoustic barriers. (1st March 2017) - Arenas, C.; Luna-Galiano, Y.; Leiva, C.; Vilches, L.F.; Arroyo, F.; Villegas, R.; Fernández-Pereira, C.
Graphical abstract: Highlights: Double objective: to recycle residues and reduce the noise in geopolymer concrete. Two residues: fly ashes and construction and demolition waste in great proportions. Sound absorption and mechanical properties similar to commercial products. Abstract: The present study aims to determine and evaluate the applicability of a new product consisting of a fly ash-based geopolymeric porous concrete with construction and demolition wastes as aggregates in the field of road noise barriers. In this work the main physical, mechanical and acoustic properties of a fly ash-based geopolymeric concrete were analyzed. To develop a porous matrix that absorbs the sound energy, two different aggregates were studied, crushed granite (usually utilized in concretes) and construction and demolition waste. The geopolymeric concretes were prepared using sodium silicate and sodium hydroxide in two different proportions in order to study the influence of the Na2 O/SiO2 ratio in the properties. The geopolymer/aggregate ratio was studied as well. The construction and demolition waste used as aggregate in geopolymeric porous concretes presents better mechanical and acoustic properties than the crushed-granite aggregates in geopolymeric concretes. The activating solution in the geopolymerization of the fly ash has a significant influence in the mechanical properties mainly but not in the acoustic properties. From an environmental point of view, the use of fly ashes and construction and demolition waste in these materials do not present any leaching problem.